PENGELOLAAN DESTINASI WISATA BERBASIS BUDAYA DI KOTA SINGKAWANG UNTUK MENINGKATKAN PARIWISATA BERKELANJUTAN (STUDI KASUS PERHELATAN BUDAYA CAP GO MEH DI KOTA SINGKAWANG) - Wicaksono, Heri; Ardita, Leonardo; Rahmadani, Annisa (Jurnal Pariwisata Indonesia, 2024)
This research explores the role of local community participation in tourism development, with a focus on the Cap Go Meh festival in Singkawang. The main objective is to assess how government and community involvement can improve sustainable tourism while preserving local culture and identity. This research uses an empirical method approach, utilizing primary data collected through questionnaires, interviews and secondary data from literature to analyze the impact of tourism on local communities. Research results show that while tourism presents economic opportunities, many local residents remain unaware of its benefits, highlighting a significant gap in understanding. This research emphasizes the need to integrate local cultural elements into tourism strategies to foster a sense of belonging among residents. It also addresses challenges such as social conflict and the need for better marketing to attract visitors. Conclusions drawn from this research indicate effective tourism development requires a collaborative approach involving local stakeholders, including government, business and community members. Recommendations include increasing public education about the benefits of tourism and promoting cultural heritage as a major attraction. By prioritizing local engagement and sustainable tourism, this research suggests that tourism can be a powerful tool for economic growth and cultural preservation, ultimately leading to more enriching experiences for visitors and local residents. This holistic approach is very important to ensure that tourism development is in line with the aspirations and needs of the community, encouraging a sustainable tourism model in Singkawang City.